The Causal Dynamics in Indian Agriculture Commodity Prices and Macro-Economic Variables in the Presence of a Structural Break. Issue 1 (February 2020) - Bodhanwala, Shernaz; Purohit, Harsh; Choudhary, Nidhi
Agriculture commodity prices have been quite volatile in India. The proposed study explores the effect of structural change on the flow of information between the spot and futures market of agriculture commodities and select macro-economic factors. The volatility in agriculture commodity prices is studied with respect to three dominant macro-economic factors—movement in crude price which serves as an input to agriculture sector, movement in INR/USD exchange rate and movement in Sensex which is considered as a barometer of investment in India. The study uses non-linear cointegration and causality test to understand the direction of causality in volatility of commodities and impact of macro-economic factors. The study observed the agriculture commodities spot and futures prices to be co-integrated with crude, forex and Sensex for majority of the break periods. We find robust evidence that futures market played a leading role in the price discovery function and information processing. Breaks in agriculture commodity prices are attributed to fundamentals of demand and supply in the market and global financial turmoil of 2007. We observed mixed results of influence of the exchange rate, Sensex and crude on agriculture prices in different sub-periods.